The Implementation of Project Based Learning Model Through English Drama Performance at 5th Semester Students of STBA JIA Bekasi - Panjaitan, Esterria Romauli; Mandela, Fitra; Lutfiyanti, Winda (PROJECT (Professional Journal of English Education), 2025)
This study at STBA JIA seeks to cultivate students’ creativity and critical thinking by implementing Project-Based Learning (PjBL) through English drama performances. It was chosen as it offers students opportunities to enhance their English speaking, listening, reading, and writing skills. Likewise, English drama encourages collaboration, creativity, and a deep understanding of cultural and literary contexts, helping students connect classical themes with modern social issues. This drama project specifically utilizes Oscar Wilde's plays, including An Ideal Husband, The Importance of Being Earnest, and Lady Windermere's Fan and conducted in CGV Cinema Bekasi. This study covered several stages which proposed by Kemendikbud (2013), namely planning, rehearsals, and final performance, all of that were monitored and evaluated by lecturers. The findings show that English Drama Project effectively encourages active student participation in the learning process, raises collaboration, and improves management skill, language skill and critical thinking skill, and even gaining confidence and responsibility. However, problems such as time limits, a lack of acting experience, and insufficient facilities were experienced. Suggested solutions are more acting training and better group collaboration. These findings help to further the development of interactive learning methods in literature study in higher education, like STBA JIA.